The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10443-011-9238-3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigations on Mechanical Behavior of Composite Corrugated Core

Abstract: Tensile and flexural characteristics of corrugated laminate panels were studied using numerical and analytical methods and compared with experimental data. Prepreg laminates of glass fiber plain woven cloth were hand-laid by use of a heat gun to ease the creation of the panel. The corrugated panels were then manufactured by using a trapezoidal machined aluminium mould. First, a series of simple tension tests were performed on standard samples to evaluate the material characteristics. Next, the corrugated panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 5 publications
0
34
0
Order By: Relevance
“…As an extension to this work, Dayyani et al [38] studied the tensile behaviour of corrugated laminates made of plain woven glass/epoxy. Contrary to the literature they observed the occurrence of delamination in all of the members of the corrugated unit cell, not only to the corner regions, and evidence that the three-stage mechanical behavior of composite corrugated core is not confined to aramid laminates and can be observed in other types of laminates.…”
Section: -1-2 Tensilementioning
confidence: 96%
See 1 more Smart Citation
“…As an extension to this work, Dayyani et al [38] studied the tensile behaviour of corrugated laminates made of plain woven glass/epoxy. Contrary to the literature they observed the occurrence of delamination in all of the members of the corrugated unit cell, not only to the corner regions, and evidence that the three-stage mechanical behavior of composite corrugated core is not confined to aramid laminates and can be observed in other types of laminates.…”
Section: -1-2 Tensilementioning
confidence: 96%
“…Dayyani et al [38] studied the flexural characteristics of a composite corrugated sheet using numerical and analytical methods and validated the results by comparing them to the experimental data. A good degree of correlation was observed in their work which evidenced the suitability of the analytical method and finite element model to predict the mechanical behaviour of the corrugated sheet in the linear and nonlinear phases of deformation.…”
Section: -1-1 Bendingmentioning
confidence: 97%
“…It is worth noting at this time that this study strictly focuses on a sinusoidal corrugated structure. This sinusoidal corrugated geometry is commonly used in the study of corrugated materials, [12][13][14]18,[21][22][23][24][25][26][27][28][29][30][31] however it is not the only corrugated geometry used and many other studies use trapezoidal corrugations, [15,19,20] and circular corrugations. [14][15][16] All of these corrugation geometries display similar increasing work hardening behavior when loaded in tension and the main difference between the geometries lies in the manner and location in which the unbending is focused, the amount of force required to unbend to a certain degree and the corresponding strain at which complete unbending has occurred.…”
Section: Modeling Proceduresmentioning
confidence: 99%
“…Utilization of the corrugated geometry has been shown to have potential to increase the necking strain of a material as a result of the unbending of the corrugation during loading. As outlined in the review paper by Dayyani et al, [10] this improved elongation in the longitudinal direction coupled with high transverse stiffness has made the corrugated geometry an excellent candidate in the construction industry, the packaging industry in the form of corrugated board, as explored in Luo et al [11] and Gilchrist et al, [12] and more recently in the aerospace industry for use in morphing wings, as studied by Ge et al, [13] Xia et al, [14] Kress and Winkler, [15] Yokozeki et al, [16] and Park et al [17] Studies of isolated corrugations or corrugated sandwich structures by Thill et al, [18] Dayyani et al, [19] Bouaziz, [20] Boke, [21] and Fraser et al [22] found that when subjected to a tensile load the stress-strain response is characterized by initially low levels of stress followed by increasing work hardening behavior that can be attributed to the unbending corrugation, followed by normal plastic behavior of the material once the corrugation is straightened. Ultimately, this leads to the material necking at a larger value of strain compared to a straight sample.…”
Section: Introductionmentioning
confidence: 99%
“…Honeycomb is lightweight, high flexural stiffness and can support classical loadings like tension and bending. Applications of corrugated-core sandwich structure have been used in aerospace and automotive industries, marine ship and civil due to their high strength to weight ratio [6][9] [15]. Previously, Mohammadi et al [16] proposed analytical formulation for trapezoidal corrugated panels.…”
Section: Introductionmentioning
confidence: 99%